Assessment of the Ability to Seal the Apex Using Gutta-Percha Combined with Bio-C Sealer, Activ GP with Bio-C Sealer, and Activ GP with Activ GP Sealer as Materials for Root Canal Filling: A Stereomicroscopic Study conducted in vitro - Arto, Mona Ismail; Mansoor, Sharif (International Journal of Environment, Agriculture and Biotechnology, 2024)
Fifty freshly extracted human permanent mandibular single-rooted premolar teeth were utilized in this study. The anatomical crowns of the chosen teeth were removed with a diamond disc, and pulp tissue was eliminated using barbed broaches. The working length was established by subtracting 0.5mm from the length determined with the tip of the trial file just visible at the apical foramen of each root canal in all specimens. Biomechanical preparation was conducted in all specimens using the crown-down technique with the ProTaper Next rotary file system. The master apical file was set to X4 (Size 40 and 6% Taper). The specimens were randomly assigned to five groups, each comprising 10 specimens. Group 1 utilized Master Gutta-percha points coated with Bio-C sealer, Group 2 used Master Activ GP points coated with Bio-C sealer, and Group 3 employed Master Activ GP points coated with Activ GP sealer as obturation materials with a single-cone technique. Group 4 served as the Negative control, with root canals left unobturated, while Group 5 served as the Positive control, using Master Gutta-percha points without any root canal sealer as the obturation material. All canal orifices were sealed with restorative Glass ionomer cement. Subsequently, specimens were double-coated with nail varnish, except for the apical 3mm of roots, and immersed in petri dishes containing Indian ink dye for 48 hours. After dye removal, nail varnish was completely eliminated, and specimens were longitudinally sectioned with a diamond disk. For each specimen, the half containing the most visible part of the entire root canal was selected, and the extent of linear dye penetration was measured using a Stereomicroscope following Escobar’s criteria. The measurements were recorded, tabulated, and statistically analyzed using One Way ANOVA and Tukey’s Post-hoc tests. Gutta-percha coated with Bio-C sealer as a root canal obturation material exhibited the highest apical sealing ability compared to Activ GP with Bio-C sealer and Activ GP with Activ GP sealer. Activ GP with Activ GP sealer displayed the lowest or poorest apical sealing ability.